Adhesive composites and methods of use thereof
By using the adhesion composite of acrylic resin and solid resin particles, the problem of easy failure in the adhesion process is solved, and the effect of improving the bonding strength and process yield between the grains and the substrate is achieved.
Patent Information
- Application Number
- CN202110453040.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-04-26
AI Technical Summary
In the prior art, the cement-adhesive process is prone to failure, which makes it difficult to improve the overall process yield of integrated circuit components. Especially when the grains become thinner and thinner, a slight difference in the thickness of the bonding line will cause the grains to be damaged, fall off, tilt or warped.
An adhesion composite including an acrylic resin and solid resin particles is adopted. The acrylic resin contains an acrylic monomer and a curing agent. The particle size of the solid resin particles is between 10 microns and 30 microns and the melting temperature is between 130 degrees Celsius and 160 degrees Celsius. The mixture is uniformly mixed and solidified by heating to form a peel strength between 10 kg and 25 kg.
Effectively adjust and balance the internal stress between the grain and the substrate, reduce the risk of grain rupture or damage, improve the bonding strength between the grain and the substrate, reduce the chance of grain falling off, tilting or warping, improve the yield of the crystal sticking process and reduce production costs.
Smart Images

Figure CN115247038B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive compound and a method for using the same, and in particular to an adhesive compound and a method for using the same applied to a die packaging process. Background Art
[0002] The semiconductor package generally refers to the wafer that has been processed in the front end of the semiconductor, and after processes such as sawing, pick-up, die bonding, and wire bonding, the cut die is coated with packaging materials to protect the durability and service life of the completed integrated circuit (IC) components (such as chips), and is easy to be widely used in circuit board assembly. Although the die bonding process in the above steps is only one of the many processes in the semiconductor back-end packaging, with the popularization of revolutionary materials such as gallium nitride (GaN) and silicon carbide (SiC) in the 5G era, terminal electronic products are increasingly demanding thin and short applications, and their related packaging technologies are gradually developing towards miniaturization. The most difficult part of the die bonding process is how to use the least amount of medium to accurately fix the die on the substrate or stack the die to the thinnest thickness, and to achieve electrical distortion and pass various reliability tests. At this time, how to avoid abnormalities such as die displacement or shedding is the key.
[0003] In the prior art, adhesives suitable for electronic packaging applications usually have good mechanical strength characteristics, and with the trend of chip miniaturization, various packaging types have been extended, such as quad flat no-lead (QFN), double flat no-lead (DFN), dual in-line package (DIP), small plastic quad flat package (QFP), small outline transistor (SOT), small outline integrated circuit (SOIC), etc. Among them, especially for the precise control of bond line thickness (BLT), if the bond line thickness is too thin, it is easy to cause the die to fall off the substrate due to poor adhesion of the die surface and / or the substrate, or excessive stress inside the resin of the adhesive. If the bond line thickness is too thick or uneven, the adhesive is easy to form a large fillet that overflows onto the top of the die, thereby contaminating the top of the die and causing trouble and inconvenience in the subsequent wire bonding process.
[0004] However, as semiconductor die become thinner and thinner, during the bonding or stacking process between the die and the substrate, the slight difference in the thickness of the bonding line may cause excessive pressure to be applied to the die, causing the die to be damaged, fall off, tilt or warp, and ultimately lead to die bonding failure, and it is difficult to improve the overall process yield of integrated circuit components.
[0005] Therefore, how to design an adhesive composite and its use method, especially to solve the technical problems of the prior art that the die bonding process is prone to failure and the overall process yield of integrated circuit components is difficult to improve, is an important topic studied by the inventors of this case. Summary of the invention
[0006] One of the purposes of the present invention is to provide an adhesive composite that can solve the technical problems of the prior art that die bonding is prone to failure and the overall process yield of integrated circuit components is difficult to improve, thereby achieving the purpose of improving the process yield and reducing production costs.
[0007] In order to achieve the above-mentioned purpose, the adhesive composite proposed in the present invention is applied to the crystal grain, and the adhesive composite includes: acrylic resin and solid resin particles. The acrylic resin includes acrylic monomer and curing agent. The solid resin particles are arranged in the acrylic resin and support the crystal grain. The weight of the acrylic monomer accounts for ≧80 and <100 of the acrylic resin, and the weight of the solid resin particles relative to the acrylic resin is >0 and ≦30. After the acrylic resin and the molten solid resin particles are uniformly mixed, they are heated to the curing temperature so that the peel strength between the crystal grain and the substrate is between 10 kg and 25 kg.
[0008] Furthermore, in the adhesive composite, the solid resin particles include bismaleimide resin, and the particle size of the solid resin particles is between 10 microns and 30 microns.
[0009] Furthermore, in the adhesive composite, the melting temperature of the solid resin particles is between 130 degrees Celsius and 160 degrees Celsius.
[0010] Furthermore, in the adhesive composite, the curing temperature is between 150 degrees Celsius and 175 degrees Celsius.
[0011] Furthermore, in the adhesive composite, the curing agent is a peroxide, and the curing agent accounts for 2 parts by weight of the acrylic resin.
[0012] Furthermore, in the adhesive composite, the grain size is 2*2 square millimeters, and the substrate is composed of copper metal or its alloy.
[0013] Another object of the present invention is to provide a method for using an adhesive composite, which can solve the technical problems of the prior art that die bonding is prone to failure and the overall process yield of integrated circuit components is difficult to improve, thereby achieving the purpose of improving the process yield and reducing production costs.
[0014] In order to achieve the above-mentioned purpose, the adhesive composite proposed by the present invention is applied to the crystal grain, and the method for using the adhesive composite includes the following steps: solid resin particles are arranged in an acrylic resin to form an adhesive composite, and the acrylic resin includes an acrylic monomer and a curing agent. The crystal grain is covered on the adhesive composite, and the solid resin particles are sandwiched between the crystal grain and the substrate. The adhesive composite is heated to the melting temperature of the solid resin particles so that the acrylic resin and the molten solid resin particles are evenly mixed. The adhesive composite is heated to the curing temperature for a curing reaction so that the crystal grain and the substrate have a peel strength between 10 kg and 25 kg. Among them, the weight of the acrylic monomer accounts for ≧80 and <100 of the acrylic resin, and the weight of the solid resin particles relative to the acrylic resin is >0 and ≦30.
[0015] Furthermore, in the method for using the adhesive composite, the solid resin particles include bismaleimide resin, and the particle size of the solid resin particles is between 10 microns and 30 microns.
[0016] Furthermore, in the method for using the adhesive composite, the melting temperature of the solid resin particles is between 130 degrees Celsius and 160 degrees Celsius, and the curing temperature is between 150 degrees Celsius and 175 degrees Celsius.
[0017] Furthermore, in the method for using the adhesive composite, the curing agent is a peroxide, and the curing agent accounts for 2 parts by weight of the acrylic resin.
[0018] Furthermore, in the method for using the adhesive composite, the grain size is 2*2 square millimeters, and the substrate is composed of copper metal or its alloy.
[0019] When using the adhesive composite and the method for operating the adhesive composite described in the present invention, the key is to configure the solid resin particles in the acrylic resin to form the adhesive composite. The acrylic resin (such as PMMA, commonly known as acrylic glue, etc.) may include an acrylic monomer (such as methyl methacrylate (MMA)) and a curing agent (such as peroxide). The solid resin particles may be composed of bismaleimide (BMI) resin, and in particular, the bismaleimide resin may share the curing agent applicable to the acrylic monomer, so that the acrylic resin and the molten solid resin particles can be uniformly mixed, and heated to a curing temperature so that the grains and the substrate have a peel strength between 10 kg and 25 kg. The physical properties that can achieve the aforementioned peel strength must be matched with the following ratio: the weight of the acrylic monomer to the acrylic resin is ≧80 and <100, and the weight of the solid resin particles relative to the acrylic resin is >0 and ≦30. Thus, after the die is coated on the adhesive compound, the solid resin particles sandwiched between the die and the substrate can be molten by heating, and after the acrylic resin and the molten solid resin particles are uniformly mixed, the adhesive compound can be heated to a curing temperature to perform a curing reaction, and finally an integrally formed bonding structure is formed between the die and the substrate. Furthermore, since the adhesive compound does not have a contact point without bonding characteristics between the die and the substrate after the curing reaction (that is, the granular shape of the solid resin particles has disappeared), it can not only effectively adjust and balance the internal stress between the die and the substrate, making the die less likely to break or be damaged, but also the molten solid resin particles can strengthen the peel strength between the die and the substrate after curing, thereby reducing the probability of the die falling off, tilting or warping from the substrate, and can well control the bondline thickness (BLT), and effectively improve the yield of the die bonding process.
[0020] To this end, the adhesive composite and its use method described in the present invention can solve the technical problems of the prior art that the die bonding process is prone to failure and the overall process yield of integrated circuit components is difficult to improve, so that the die and the substrate can be more tightly bonded, thereby achieving the purpose of improving the process yield and reducing production costs.
[0021] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but is not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the structure of the adhesive composite of the present invention before the curing reaction;
[0023] Figure 2is a schematic diagram of the structure of the adhesive composite of the present invention after the curing reaction; and
[0024] Figure 3 The figure is a flow chart of the method for using the adhesive composite of the present invention.
[0025] Wherein, the reference numerals are:
[0026] 1: Acrylic resin
[0027] 2: Solid resin particles
[0028] 3: Bonding structure
[0029] 11: Touchpoints
[0030] 100: Grain
[0031] 200:Substrate
[0032] S1~S4: Steps DETAILED DESCRIPTION
[0033] The following describes the implementation of the present invention by means of specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents provided in this specification. The present invention can also be implemented or applied by means of other different specific examples, and the details in the present invention specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0034] It should be noted that the structures, proportions, sizes, number of components, etc. illustrated in the drawings of this specification are only used to match the contents provided in the specification so that people familiar with this technology can understand and read them. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportional relationship or adjustment of size should fall within the scope of the technical content provided by the present invention without affecting the effects and purposes that can be achieved by the present invention.
[0035] The technical content and detailed description of the present invention are described as follows with reference to the accompanying drawings.
[0036] See also Figure 1 as well as Figure 2 As shown, Figure 1 It is a schematic diagram of the structure of the adhesive composite of the present invention before the curing reaction. Figure 2 It is a schematic diagram of the structure of the adhesive composite of the present invention after the curing reaction.
[0037] In one embodiment of the present invention, the adhesive composite proposed by the present invention is applied to a die 100, and the adhesive composite includes: an acrylic resin 1 and solid resin particles 2. The acrylic resin 1 may include an acrylic monomer (not shown in the figure, for example: methyl acrylate, ethyl acrylate, n-butyl acrylate and methyl methacrylate (MMA), n-butyl methacrylate, etc.) and a curing agent (not shown in the figure). The weight of the acrylic monomer in the acrylic resin 1 is ≧80 and <100. For example, the acrylic resin 1 may include a thermosetting acrylic resin or a thermoplastic acrylic resin. The thermosetting acrylic resin is an infusible acrylic polymer with an acrylic monomer as a basic component and cross-linked into a network structure. In addition to the general properties of acrylic resin, it has better heat resistance, water resistance, solvent resistance, wear resistance, and scratch resistance (anti-scratch property), and has a variety of forms such as bulk casting material, solution type, emulsion type, and water-based type. The cross-linking methods are divided into two categories: (1) the functional groups in the reactive cross-linking polymer have no cross-linking reaction ability; or (2) the self-cross-linking polymer chain itself contains two or more reactive functional groups. The thermoplastic acrylic resin is a type of thermoplastic resin made by polymerizing acrylic acid, methacrylic acid and its derivatives (such as esters, nitriles, and amides). It can be repeatedly softened by heat and solidified by cooling. It is generally a linear polymer compound, which can be a homopolymer or a copolymer, with good physical and mechanical properties, excellent weather resistance, chemical resistance and water resistance, and high gloss and color retention. The molecular weight of the thermoplastic acrylic resin used in the coating industry is generally 75,000 to 120,000, and nitrocellulose, cellulose acetate butyrate and perchlorethylene resin are often used in combination with it to improve the coating performance. Thermoplastic acrylic resin is a type of solvent-based acrylic resin that can be melted and dissolved in an appropriate solvent. The coating prepared by it forms a film by the aggregation of macromolecules after the solvent evaporates. No cross-linking reaction occurs during film formation, and it is a non-reactive coating. In order to achieve better physical and chemical properties, the molecular weight of the resin should be increased, but in order to ensure that the total amount of non-volatile substances is not too low and the molecular weight is not too large, generally, when the molecular weight is tens of thousands, the physical and chemical properties and construction performance are relatively balanced. In the embodiment of the present invention, the acrylic resin 1 can be polymethyl methacrylate (PMMA), also known as acrylic or organic glass, and its corresponding acrylic monomer is methyl methacrylate (MMA).
[0038] Furthermore, the adhesive composite may further include a dispersant, which may be uniformly mixed with the acrylic monomer in the acrylic resin 1 simultaneously or sequentially. Adding the dispersant can prevent the agglomeration or sedimentation of the material molecules, make the physical properties of the material more uniform, and obtain the acrylic resin 1 with uniform physical properties during the subsequent degradation (such as roller mill dispersion, which may cause the bond between the material molecules to break). Dispersants are generally divided into two categories: inorganic dispersants and organic dispersants. Commonly used inorganic dispersants include silicates (such as water glass) and alkali metal phosphates (such as sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate). Organic dispersants include triethylhexyl phosphate, sodium dodecyl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide, gum, fatty acid polyethylene glycol esters, etc. In addition, the curing temperature of the acrylic resin 1 may be between 150 degrees Celsius and 200 degrees Celsius. Furthermore, the curing condition of the acrylic resin 1 may be 175 degrees Celsius and continuous heating for 60 minutes. In the embodiment of the present invention, the ratio of the dispersant to the acrylic resin 1 may be less than 1 wt %.
[0039] The solid resin particles 2 are arranged in the acrylic resin 1 and are used to support the crystal grains 100 on the substrate 200. In the embodiment of the present invention, the solid resin particles 2 may be composed of bismaleimide (BMI) resin, and the particle size of the solid resin particles 2 is between 10 microns and 30 microns, the melting temperature of the solid resin particles 2 is between 130 degrees Celsius and 160 degrees Celsius, and the curing temperature may preferably be between 150 degrees Celsius and 175 degrees Celsius. The bismaleimide (BMI) is a bifunctional compound, and its biactive end groups are maleimide (maleimide and imide), and the BMI has the characteristics of heat resistance, weather resistance, and moisture resistance of polyimide resin, and also has radiation resistance and good dielectric properties, and has physical properties and molding processing methods equivalent to epoxy resin. In particular, the bismaleimide resin can share the curing agent applicable to acrylic monomers, so that the acrylic resin 1 and the molten solid resin particles 2 can be uniformly mixed and then cured together to form an integrally formed bonding structure 3, thereby strengthening the bonding strength between the grain 100 and the substrate 200. The weight of the solid resin particles 2 relative to the acrylic resin 1 is greater than 0 and less than 30. In the embodiment of the present invention, the curing agent is a peroxide with strong oxidizing properties, and the curing agent accounts for 2 parts by weight of the acrylic resin 1. After the acrylic resin 1 and the molten solid resin particles 2 are uniformly mixed and heated to the curing temperature, the peel strength between the grain 100 and the substrate 200 can be between 10 kg and 25 kg. The conditions for achieving the above effect also include that the grain 100 is 2*2 square millimeters in size and the substrate 200 is composed of copper metal or its alloy.
[0040] See also Figure 3As shown, it is a flow chart of the method for using the adhesive composite of the present invention. When using the adhesive composite of the present invention and operating the method for using the adhesive composite, the key is to configure the solid resin particles 2 in the acrylic resin 1 to form the adhesive composite (step S1). Then, the die 100 is covered on the adhesive composite, and the solid resin particles 2 are sandwiched between the die 100 and the substrate 200 (step S2), and at this time, there is a contact point 11 without bonding properties between the die 100 and the substrate 200. The acrylic resin 1 (such as PMMA commonly known as acrylic glue, etc.) may include an acrylic monomer (such as methyl methacrylate (MMA)) and a curing agent (such as peroxide). The solid resin particles 2 may be made of bismaleimide (BMI) resin, and in particular, the bismaleimide resin may share the curing agent applicable to acrylic monomers, so that the acrylic resin 1 and the molten solid resin particles 2 are uniformly mixed and heated to a curing temperature so that the peel strength between the crystal grain 100 and the substrate 200 is between 10 kg and 25 kg. The physical properties that can achieve the above-mentioned peel strength must be matched with the following ratio: the weight of the acrylic monomer to the acrylic resin 1 is ≧80 and <100, and the weight of the solid resin particles 2 relative to the acrylic resin 1 is >0 and ≦30. Thus, after the die 100 is covered on the adhesive composite, the solid resin particles 2 sandwiched between the die 100 and the substrate 200 can be molten by heating, and after the acrylic resin 1 and the molten solid resin particles 2 are evenly mixed (step S3), the adhesive composite can be heated to a curing temperature to perform a curing reaction (step S4), and finally an integrally formed bonding structure 3 is formed between the die 100 and the substrate 200. Furthermore, since the adhesive composite does not have a contact point 11 without bonding properties between the die 100 and the substrate 200 after the curing reaction (that is, the granular shape of the solid resin particles 2 has disappeared), it can not only effectively adjust and balance the internal stress between the die 100 and the substrate 200, so that the die 100 is not easily broken or damaged, but also the molten solid resin particles 2 can strengthen the peeling strength between the die 100 and the substrate 200 after curing, thereby reducing the probability of the die 100 falling off, tilting or warping from the substrate 200, and can well control the bond line thickness (BLT), and effectively improve the yield of the die bonding process.
[0041] To this end, the adhesive composite and its use method described in the present invention can solve the technical problems of the prior art that the die bonding process is prone to failure and the overall process yield of integrated circuit components is difficult to improve, so that the die 100 and the substrate 200 can be more tightly bonded, thereby achieving the purpose of improving the process yield and reducing production costs.
[0042] Finally, the following table shows four formulations and a control group in the embodiments of the present invention:
[0043]
[0044] It can be seen from the above table that in the four formulations, the bonding structure 3 solidified after the solid resin particles 2 are melted can significantly enhance the peel strength between the die 100 and the substrate 200, making the peel strength between the die 100 and the substrate 200 better than that of the control group.
[0045] The above description is only a detailed description and drawings of the preferred specific embodiments of the present invention, but the features of the present invention are not limited thereto and are not intended to limit the present invention. The entire scope of the present invention shall be subject to the following claims. All embodiments that conform to the spirit of the claims of the present invention and similar variations thereof shall be included in the scope of the present invention. Any changes or modifications that can be easily conceived by a person familiar with the art within the field of the present invention shall be covered by the patent scope of the following case.
[0046] It should be noted that the structures, proportions, sizes, number of components, etc. illustrated in the drawings of this specification are only used to match the contents provided in the specification so that people familiar with this technology can understand and read them. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportional relationship or adjustment of size should fall within the scope of the technical content provided by the present invention without affecting the effects and purposes that can be achieved by the present invention.
Claims
1. An adhesive composite, applied to a die, characterized in that: include: an acrylic resin comprising an acrylic monomer and a curing agent; and A solid resin particle is disposed in the acrylic resin and supports the crystal grain; The acrylic monomer is methyl methacrylate, and relative to 100 parts by weight of the acrylic resin, the weight of the acrylic monomer is ≧80 and <100, and the weight of the solid resin particles is >0 and ≦30; The solid resin particles include bismaleimide resin, which is a bifunctional compound, whose biactive end groups are maleimide, and whose melting temperature is between 130 degrees Celsius and 160 degrees Celsius; wherein, after the acrylic resin is uniformly mixed with the molten solid resin particles, it is heated to a curing temperature so that the peel strength between the crystal particles and a substrate is between 10 kg and 25 kg; The particle size of the solid resin particles is between 10 microns and 30 microns.
2. The adhesive composite according to claim 1, characterized in that The curing temperature is between 150 degrees Celsius and 175 degrees Celsius.
3. The adhesive composite according to claim 1, characterized in that The curing agent is a peroxide, and the weight portion of the curing agent is 2 parts relative to 100 parts by weight of the acrylic resin.
4. The adhesive composite according to claim 1, characterized in that The grain size is 2*2 square millimeters, and the substrate is made of copper metal or its alloy.
5. A method of using an adhesive compound, wherein the adhesive compound is applied to a die, characterized in that: The method of use includes: Disposing a solid resin particle in an acrylic resin to form the adhesive composite, wherein the acrylic resin includes an acrylic monomer and a curing agent; The die is covered on the adhesive compound, and the solid resin particles are sandwiched between the die and a substrate; heating the adhesive composite to a melting temperature of the solid resin particles to uniformly mix the acrylic resin with the melted solid resin particles; and The adhesive composite is heated to a curing temperature to perform a curing reaction so that the peel strength between the die and the substrate is between 10 kg and 25 kg; Wherein, the solid resin particles include bismaleimide resin, and the melting temperature is between 130 degrees Celsius and 160 degrees Celsius; The acrylic monomer is methyl methacrylate, and relative to 100 parts by weight of the acrylic resin, the weight of the acrylic monomer is ≧80 and <100, and the weight of the solid resin particles is >0 and ≦30; The particle size of the solid resin particles is between 10 microns and 30 microns.
6. The method for using the adhesive composite according to claim 5, characterized in that: The curing temperature is between 150 degrees Celsius and 175 degrees Celsius.
7. The method for using the adhesive composite according to claim 5, characterized in that: The curing agent is a peroxide, and the weight portion of the curing agent is 2 parts relative to 100 parts by weight of the acrylic resin.
8. The method for using the adhesive composite according to claim 5, characterized in that: The grain size is 2*2 square millimeters, and the substrate is made of copper metal or its alloy.
Citation Information
Patent Citations
Chip adhesive with low resin precipitation and preparation method of chip adhesive
CN107353855A
Resin composition and semiconductor device
JP2011204902A